Optimization of Packaging Design for Bumbu Pecel Putri Srikandi Using the Quality Function Deployment (QFD) Method - Tutuko, Putri Kinanti Ayu Hapsari; Nurdiansyah, Rudi (Universitas Muhammadiyah Sidoarjo, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesia economy, contributing over 60% to GDP and employing nearly 97% of the workforce. Competitiveness can be improved through packaging that protects product, strengthens brand identity, and attracts consumers. Putri Srikandi, a traditional peanut sauce (bumbu pecel) producer, still uses simple plastic packaging, limiting its market appeal. This study redesigns the packaging using Quality Function Deployment (QFD) through House of Quality (HoQ) to translate consumer preferences into technical specifications. Data from 112 respondents identify 13 key attributes, with readable font color (A3) and eco-friendly packaging (A5) scoring the highest (4.13), while attractive packaging design (A1) and hygiene (A12) scored the lowest (3.96). Benchmarking shows the product underperforms compared to competitors. HoQ analysis produces 13 technical responses, with top priorities are clear producer information (A6, RW = 7.75; NRW = 9%), and brand/logo visibility (A8, RW = 7.71; NRW = 8%). The final design integrates modern aesthetics, local identity, spiciness-based color coding, and eco-friendly materials to enhance competitiveness and consumer trust.